Dimensionality, party competition and voter preference in the era of populism: The case of England, 2010-2017 - Do Won Kim (London School of Economics and Political Science (LSE), European Institute, 2020)
This study examines how the UK political space, party competition and voting behaviour have changed with the recent rise of populism. First, this paper identifies the changes in UK dimensionality by conducting factor analyses on British Election Study data. Then, it maps parties and their supporters on the identified space to explore the changes in party competition and voter-party congruence. Finally, this study runs an OLS regression to analyse to what extent voter-party congruence influences voter's party preference. This study finds that UK political space has become multidimensional as issues related to populism have become salient enough to form an independent dimension. After Brexit, however, the main contents of this new dimension have changed from EU-related immigration issues to Brexit negotiation. Meanwhile, party competition and voter preferences have revolved around and placed more emphasis on the salient dimension.
Keywords: 330; Multidimensionality; populism; voter-party congruence